2017
DOI: 10.1080/13527258.2016.1277776
|View full text |Cite
|
Sign up to set email alerts
|

The heritage tourist: an understanding of the visitor experience at heritage attractions

Abstract: Please find attached the proofs for your article. 1. Please check these proofs carefully. It is the responsibility of the corresponding author to check these and approve or amend them. A second proof is not normally provided. Taylor & Francis cannot be held responsible for uncorrected errors, even if introduced during the production process. Once your corrections have been added to the article, it will be considered ready for publication Please limit changes at this stage to the correction of errors. You shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 78 publications
1
60
0
1
Order By: Relevance
“…The perception of the OUV attraction had a positive effect on place attachment H1 (β = 0.44) and heritage protection behaviour intention H2 (β = 0.36), and were moderately effective (path coefficient 0.0-0.1 is a weak effect, 0.1-0.5 was a medium effect, and 0.5-1.0 was a strong effect [102]), which showed that the core OUV attraction of the WNHS had an important influence on tourists' experience value and emotional attachment. This was consistent with the relevant research conclusions [16,17,19,29,30]. Service quality had a positive effect on place attachment H4 (β = 0.55, strong effect) and heritage protection behaviour intention H5 (β = 0.41, medium effect), indicating that the service quality of the heritage site as perceived by tourists had an important impact on their value perception, emotional attachment, environmental protection behaviour intentions and other aspects, which was consistent with the conclusions of previous relevant research [28][29][30][31]45].…”
Section: Discussion Of the Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The perception of the OUV attraction had a positive effect on place attachment H1 (β = 0.44) and heritage protection behaviour intention H2 (β = 0.36), and were moderately effective (path coefficient 0.0-0.1 is a weak effect, 0.1-0.5 was a medium effect, and 0.5-1.0 was a strong effect [102]), which showed that the core OUV attraction of the WNHS had an important influence on tourists' experience value and emotional attachment. This was consistent with the relevant research conclusions [16,17,19,29,30]. Service quality had a positive effect on place attachment H4 (β = 0.55, strong effect) and heritage protection behaviour intention H5 (β = 0.41, medium effect), indicating that the service quality of the heritage site as perceived by tourists had an important impact on their value perception, emotional attachment, environmental protection behaviour intentions and other aspects, which was consistent with the conclusions of previous relevant research [28][29][30][31]45].…”
Section: Discussion Of the Resultssupporting
confidence: 93%
“…Researchers have mainly emphasised the value of OUV from the perspective of the OUV attraction [14,15]. From the perspective of active brand marketing, an OUV attraction can attract tourists and generate public attention [16,17]. Destination attraction has a positive effect on place attachment and helps to promote heritage protection [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Prior the visit, tourists have some motivations leading to the expectation of having a meaningful experience and the information based on decision making. In this phase, advice from friends and relatives is very important despite social media (Kempiak et al, 2017). During the in situ visitations, the information, communication, engagement, and atmosphere are important points.…”
Section: Understanding Touristic Attractionsmentioning
confidence: 99%
“…During the in situ visitations, the information, communication, engagement, and atmosphere are important points. In a post visitation, the visitors value the duration, knowledge acquisition, and generate a level of satisfaction that may stimulate a re-visitation on other occasions (Kempiak et al, 2017).…”
Section: Understanding Touristic Attractionsmentioning
confidence: 99%
“…The architectural models of DeCACHe and the cognition-centered framework not only support the complementation with other components, as discussed in the previous section, but also support the integration of other personalization factors besides cognition. Such factors reflect on various aspects that influence the visitor experience [58,59] such as intrinsic motivations [60], perceived quality of the CH experience [61], and emotional connection [62]. Personalization factors that can be used in combination with cognition are: visitor location [63], interests [64], social behavior [65], background knowledge [66], preferences [67], motivation [68], themes [69], mood [70], visiting style [71], visit and viewing time [72], visit history [73], and disabilities [74].…”
Section: Combining Cognition With Other Personalization Factorsmentioning
confidence: 99%